Administration of the Patent System in Sri Lanka: A Critical Appraisal. (December 2014) - Perera, Asanka
The administration of the patent system in Sri Lanka and its importance to the national economic strategy is a novel topic in the country. The national patent law in Sri Lanka has been subject to international agreements such as the WTO TRIPS Agreement and the WIPO Patent Cooperation Treaty. Nevertheless, Sri Lanka is notable for the undeveloped state of its patent system, mainly because the patent examination system is not designed or based on national or economic priorities. With this background, the purpose of this paper is to examine and critically evaluate the different mechanisms adopted in the patent administration system and whether the present patent system in Sri Lanka remains aligned with Sri Lanka's national economic strategy and how the present system could be developed to strengthen the patent system, both in provision and in administration. The paper recommends that Sri Lanka is better off having a utility model system along with a high standard of patent examination system. By employing this dual system both domestic innovation and foreign investment would increase in the future.